2016
DOI: 10.1021/acs.est.6b00484
|View full text |Cite
|
Sign up to set email alerts
|

Sulfation of Lower Chlorinated Polychlorinated Biphenyls Increases Their Affinity for the Major Drug-Binding Sites of Human Serum Albumin

Abstract: The disposition of toxicants is often affected by their binding to serum proteins, of which the most abundant in humans is serum albumin (HSA). There is increasing interest in the toxicities of environmentally persistent polychlorinated biphenyls (PCBs) with lower numbers of chlorine atoms (LC-PCBs) due to their presence in both indoor and outdoor air. PCB sulfates derived from metabolic hydroxylation and sulfation of LC-PCBs have been implicated in endocrine disruption due to high affinity-binding to the thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 63 publications
(132 reference statements)
0
36
0
Order By: Relevance
“…Similarly, more research is required to expand our current knowledge about potential bioactivities associated with these sulfate metabolites. Previous studies have clearly indicated the potential of PCB sulfates to interact with two major serum transport proteins, albumin (Rodriguez et al 2016) and TTR (Grimm et al 2013, 2015c) in vitro . Binding affinities to both proteins suggest potential mechanisms for the retention and inter-tissue transport of PCB metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, more research is required to expand our current knowledge about potential bioactivities associated with these sulfate metabolites. Previous studies have clearly indicated the potential of PCB sulfates to interact with two major serum transport proteins, albumin (Rodriguez et al 2016) and TTR (Grimm et al 2013, 2015c) in vitro . Binding affinities to both proteins suggest potential mechanisms for the retention and inter-tissue transport of PCB metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture media and cell pellets were extracted and analyzed for PCB metabolites using targeted and untargeted approaches ( Similarly, an in vitro study showed that the binding affinity of PCBs for binding site Ⅱ of albumin, the major protein in FBS, increases with an increase in the number of chlorine atoms. 52 The PCB mass ratios between cell pellets : media : dishes were 1 : 4.9 : 0.54 for pentachlorinated congeners and : 8.6 : 0.37 for hexachlorinated congeners, respectively. These ratios are comparable to earlier studies.…”
Section: Resultsmentioning
confidence: 94%
“…For example, DHEA-sulfate binds to human serum albumin with high affinity and has a halflife of 7-10 hours, while DHEA binds with much lower affinity and has a half-life of 15-30 minutes [375]. By analogy, OH-PCBs and PCB sulfates also bind with high affinity to serum proteins such as human serum albumin [42] and transthyretin [36,376].…”
Section: Figure 6-1 a Summary Of Resultsmentioning
confidence: 99%
“…The high volatility of the LC-PCBs leads to their presence in indoor air (especially older buildings) [9-11, 40, 41]. The PCB metabolites consist of hydroxylated and sulfated metabolites [35], but these metabolites are also able to elicit genotoxic effects that are produced from further metabolism into quinones and other reactive species [7,34,35,41,42].…”
Section: Lower Chlorinated Pcbs Vs Higher Chlorinated Pcbsmentioning
confidence: 99%
See 1 more Smart Citation